Towards adopting passive heat dissipation approaches for temperature regulation of PV module as a sustainable solution. (March 2017) - Elbreki, A.M.; Alghoul, M.A.; Sopian, K.; Hussein, T.
Abstract: Solar technology is a promising renewable option and essential towards a sustainable energy future. PV power systems represent a major part of solar technology. The efficiency of a PV module is limited by many factors such as ohmic losses between solar cells, solar radiation, high module temperature, dust and packing factor. A combined PV/T concept was proposed to reduce the thermal stress of PV module by recovering the heat of high PV module temperature and use it for thermal applications. After decades of continuous research and development (R&D) aspects on PV/T, many researchers reported lower PV electrical efficiency, lower thermal efficiency and lower PV/T efficiency for it than the two separate systems. That is why, the product reliability of the PV/T system does not succeed in penetrating the market due to technical, cost and size barriers such as materials, design, manufacturing techniques, initial cost, installation cost and the bulk size of the system. Since the PVT concept failed to increase the electrical and thermal efficiencies concurrently, it would be more appropriate if the R&D community refocuses its efforts again on the heat dissipation option instead of the costly heat recovery option to regulate the high PV module temperature. The aim of this review is to provide an insight into the role of passive and active techniques in the thermal regulation of PV module temperature. The study will shed light on the temperature reduction range that is possible by the available passive and active heat dissipation approaches. Also, the effectiveness of passive approaches in lowering the temperature of the PV module when compared to active approaches will be highlighted as well. In addition to this overall study, this review will include a discussion of the effectiveness of passive and active approaches in the context of PVT collector, thus supporting the argument towards the potential of passive approaches when compared to active approaches. The outcomes of this study are detailed in the lessons-learned section and future research priorities are highlighted in the conclusion section.